Absorption and dispersion in undoped epitaxial GaSb layer. (28th February 2018) - Wasiak, Michał; Motyka, Marcin; Smołka, Tristan; Ratajczak, Jacek; Jasik, Agata
Abstract: In this paper, we present the results of a theoretical and experimental investigation into the refractive index and absorption, at room temperature, of a 4 μm-thick undoped epitaxial layer of GaSb deposited on a GaAs substrate. A theoretical formula for optical transmission through an etalon was derived, taking into account the finite coherence length of the light. This formula was used to analyse the measured transmission spectra. The refractive index was determined in a wide spectral range, between 0.105 eV and 0.715 eV. The absorption was determined for photon energies between 0.28 eV and 0.95 eV. An Urbach tail was observed in the absorption spectrum, as well as a constant increase in absorption in the spectral region above the band gap.